Accounting as a Language of Business: A study for conceptual understanding (International Journal of Scientific Research and Management (IJSRM), 2017)
The study endeavors to know why accounting is called the language of business, how it deals and who need this language. To serve the objectives s of the study in-depth study in understanding about the theory of accounting, practice and open discussion with independent auditor, practitioners, different accounting recording format has been considered, the findings of the study show that accounting is the language of business in written and silence version not in orally until they been uttered in decision, different Financial Statements are the means of language.